Analisis Yuridis Hak Subjektif Para Pihak Dalam Perkara Perdata Nomor 116/PDT/2019/PT KPG. - Louisa Helena Arini Punuf; Helsina Fransiska Pello; Husni Kusuma Dinata (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the legal reasoning of the panel of judges in protecting the subjective rights of the litigating parties and to examine the legal consequences of subjective rights in Decision Number 116/PDT/2019/PT KPG concerning a land ownership dispute. The research employed a normative legal research method using statutory and case approaches. Legal materials were collected through library research consisting of primary, secondary, and tertiary legal sources and were analyzed using descriptive qualitative methods. The findings reveal that the judges' legal considerations were consistent with the Indonesian Civil Code, the Rechtsreglement voor de Buitengewesten (RBg), the Basic Agrarian Law, and the principles of justice governing evidentiary assessment. The court relied on witness testimony, on-site judicial inspection, physical evidence, and customary legal values recognized within the local community in determining the plaintiff as the lawful owner of the disputed land. Nevertheless, despite the judgment having obtained permanent legal force, the plaintiff's subjective rights have not been effectively realized due to obstacles in the execution process. This situation has resulted in legal uncertainty, ineffective legal protection for the successful party, diminished judicial authority, and potential human rights violations, along with other legal consequences. Therefore, strengthening the judicial execution mechanism is essential to ensure legal certainty, justice, and legal effectiveness